Optical film and display device
By applying Fast Fourier Transform analysis and microparticle low-refractive-index layer design to the surface of the optical film, combined with antibacterial agent components, the problem that the concave-convex shape parameters of the optical film cannot reflect complex changes was solved, and the optical properties, fingerprint erasure, antibacterial and antiviral properties were improved.
Patent Information
- Application Number
- CN202480017101.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-03-06
- Filing Date
- 2024-03-05
- Publication Date
- 2025-10-28
AI Technical Summary
The existing optical film's uneven shape parameters cannot accurately reflect the complex changes in height and spacing, resulting in insufficient correlation between optical properties and fingerprint erasure, and making it difficult to achieve both antibacterial and antiviral properties simultaneously.
By applying Fast Fourier Transform to analyze the concavity and convexity height information on the surface of the optical film, and satisfying specific power spectrum integral value conditions, combined with the design of microparticles and low refractive index layers, an appropriate concavity and convex structure is formed, and antibacterial or antiviral agents are added to the anti-glare layer.
It achieves excellent optical properties, superior fingerprint wiping properties, antibacterial and antiviral properties of optical films, simplifies the manufacturing process, and improves the overall performance of optical films.
Smart Images

Figure CN120858302A_ABST
Abstract
Description
Technical Field
[0001] This disclosure relates to optical films and display devices having optical films. Background Art
[0002] To suppress reflections around a display device, an optical film disposed on the outermost surface of the display device is known. The optical film has fine irregularities on its surface, which cause light scattering and reflective light diffusion, thus suppressing reflections. Furthermore, it is known to impart the function of suppressing the reflection of external light by stacking a low-refractive-index layer on such an optical film (see, for example, Patent Document 1).
[0003] In recent years, with the widespread adoption of display devices equipped with touch panels, the importance of fingerprint erasure, a characteristic required of optical films, has increased. High fingerprint erasure means that fingerprints attached to the optical film are easy to erase (for example, see Patent Document 2).
[0004] Furthermore, due to the recent increase in hygiene awareness, the demand for optical films with antibacterial and antiviral properties is also increasing (for example, see Patent Document 3).
[0005] Existing technical documents
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Publication No. 2012-103701
[0008] Patent Document 2: Japanese Patent Application Publication No. 2011-133905
[0009] Patent Document 3: International Publication No. 2021 / 256560 Summary of the Invention
[0010] The problem that the invention aims to solve
[0011] The surface irregularity of an optical film affects optical properties such as light scattering and fingerprint erasure. To date, parameters representing the characteristics of such irregularities, as described in Patent Documents 1 and 2, have used surface roughness such as the arithmetic mean height Sa specified in ISO 25178 and linear roughness such as the arithmetic mean roughness Ra specified in JIS B 0601. However, these surface roughnesses and linear roughnesses are parameters that express the height and spacing of the irregularities as averages and maximum values, making it difficult to accurately reflect the characteristics of irregularities with complex variations in height and spacing. In particular, it is difficult to find a high correlation between surface roughness and fingerprint erasure.
[0012] Therefore, it is desirable to specify the uneven shape using parameters that are more correlated with optical properties and fingerprint erasure, and to use such an uneven optical film to exhibit antibacterial and antiviral properties.
[0013] Methods for solving problems
[0014] This document describes various methods for solving the aforementioned problems using optical films and display devices.
[0015] [Method 1] An optical film having a surface with irregularities and containing a functional component that is at least one of an antibacterial agent and an antiviral agent, wherein when a fast Fourier transform is applied to the height information of the irregularities at various locations on the surface, the power spectrum in one direction passing through the origin satisfies the following conditions 1 and 2: (Condition 1) The integral value of the power spectrum intensity in the spatial frequency f range of 0 < f ≤ 150 cycle / mm is a first intensity integral value, and the integral value of the power spectrum intensity in the spatial frequency f range of 0 < f ≤ 300 cycle / mm is a second intensity integral value, wherein the first intensity integral value is less than 0.65 relative to the second intensity integral value; (Condition 2) The integral value of the power spectrum intensity in the spatial frequency f range of 40 cycle / mm < f < 60 cycle / mm is a third intensity integral value, wherein the third intensity integral value is 130 or greater.
[0016] Based on the above configuration, by satisfying condition 1, the periodicity of the unevenness is not excessively high, thus achieving good optical properties due to light scattering from the surface of the optical film. Furthermore, by satisfying condition 2, the height of the periodic unevenness, which is highly correlated with fingerprint erasure, can be sufficiently ensured, thereby improving fingerprint erasure. Therefore, in this optical film, at least one of antibacterial and antiviral properties, as well as good optical properties and fingerprint erasure, can be obtained.
[0017] [Method 2] The optical film according to [Method 1] has a substrate and an anti-glare layer supported by the substrate, the anti-glare layer containing microparticles and having a surface with irregularities corresponding to the dispersion of the microparticles.
[0018] Based on the above composition, the presence of microparticles creates unevenness, thus making it easy to form fine unevenness or adjust the shape of unevenness.
[0019] [Method 3] According to the optical film of [Method 2], wherein the surface of the anti-glare layer is the surface of the optical film, and the anti-glare layer contains the functional component.
[0020] Based on the above configuration, since the anti-glare layer located on the outermost surface of the optical film contains functional components, the manufacturing process of the optical film can be simplified compared to the case where the layer containing the functional components is set separately from the anti-glare layer.
[0021] [Method 4] According to [Method 2], the optical film further comprises a low refractive index layer located on the anti-glare layer, the low refractive index layer having a lower refractive index than the anti-glare layer and having a surface shape that follows the unevenness of the anti-glare layer.
[0022] Based on the above structure, light interference is generated by the stacking of low refractive index layers, thereby suppressing surface reflection of the optical film.
[0023] [Method 5] According to the optical film of [Method 4], wherein the surface of the low refractive index layer is the surface of the optical film, and at least one of the anti-glare layer and the low refractive index layer contains the functional component.
[0024] Based on the above configuration, since at least one of the anti-glare layer and the low refractive index layer contains a functional component, the manufacturing process of the optical film can be simplified compared to the case where a layer containing a functional component is separately provided outside these layers.
[0025] [Method 6] An optical film according to any one of [Method 1] to [Method 5], wherein the functional component contained in the optical film is a particle containing a metal or a metal oxide, and is at least one of particles having an average particle size of less than 1 μm and an organic material.
[0026] Based on the above structure, it is possible to suppress the functional components from being visually identified as bright spots or agglomeration points, thereby suppressing the reduction in the appearance quality of the optical film.
[0027] [Method 7] An optical film according to any one of [Method 1] to [Method 6], wherein the layer of the optical film including the surface contains an antifouling agent.
[0028] Based on the above structure, the surface of the optical film performs anti-fouling function, thus further improving fingerprint wiping performance.
[0029] [Method 8] The optical film according to [Method 7], wherein the antifouling agent comprises at least one of a fluorine compound and a silicone compound.
[0030] Based on the above composition, it can appropriately perform its anti-fouling function.
[0031] [Method 9] An optical film according to any one of [Method 1] to [Method 8], wherein the reflectance of 1° in the optical film is 90 or less, and the reflectance of 5° is 70 or more.
[0032] Based on the above configuration, good anti-glare performance can be achieved.
[0033] [Method 10] A display device comprising an optical film as described in any one of [Method 1] to [Method 9] and a display surface for displaying an image, wherein the optical film is located on the display surface.
[0034] Based on the above configuration, a display device with excellent optical properties and fingerprint-resistant properties can be obtained. In particular, if the display device is equipped with a touch panel, it can obtain greater benefits from the fingerprint-resistant, antibacterial, and antiviral properties of the optical film.
[0035] Invention Effects
[0036] According to this disclosure, antibacterial, antiviral, and good optical properties and fingerprint-removing properties can be obtained in optical films. Attached Figure Description
[0037] Figure 1 This is a diagram showing the cross-sectional structure of a first example of an optical film according to one embodiment.
[0038] Figure 2 This is a diagram showing the cross-sectional structure of a second example of an optical film in one embodiment.
[0039] Figure 3 This is a diagram showing a typical example of the power spectrum obtained by performing a fast Fourier transform on the surface of the optical film in one embodiment.
[0040] Figure 4 This is a graph showing the relationship between the integral value of the intensity in the power spectrum and the fingerprint erasability.
[0041] Figure 5 This is a diagram illustrating the configuration of a display device in one embodiment. Detailed Implementation
[0042] An embodiment of the optical film and display device will be described with reference to the accompanying drawings.
[0043] [Layer Composition of Optical Films]
[0044] Figure 1 This is a first example of the layer structure of the optical film 10. As the first example, the optical film 10A includes a substrate 11 and an anti-glare layer 12.
[0045] The substrate 11 is transparent to light in the visible region. The thickness of the substrate 11 is not particularly limited, but is preferably 20 μm or more and 200 μm or less. If the substrate 11 is 20 μm or more, the processing of the substrate 11 becomes easier, and if the substrate 11 is 200 μm or less, the thickening of the optical film 10A can be suppressed.
[0046] The material of substrate 11 is, for example, synthetic resin or inorganic glass. Synthetic resins include, for example, polyolefins, polyesters, polyacrylates, polyamides, polyimides, polyacrylates, polycarbonates, triacetyl cellulose, polyvinyl alcohol, polyvinyl chloride, cyclic olefin copolymers, norbornene resins, polyethersulfone, polysulfone, etc. Examples of polyolefins include polyethylene and polypropylene. Examples of polyesters include polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, etc. Examples of polyacrylates include polymethyl methacrylate, etc. Examples of polyamides include nylon 6, nylon 66, etc. A film formed from polyesters such as polyethylene terephthalate, triacetyl cellulose, and polymethyl methacrylate is suitable for use as substrate 11.
[0047] The anti-glare layer 12 is supported by the substrate 11, and its surface, opposite to the surface in contact with the substrate 11, has irregularities. The surface of the anti-glare layer 12 is the surface of the optical film 10A. The average thickness of the anti-glare layer 12 is preferably 1 μm or more and 30 μm or less, more preferably 3 μm or more and 15 μm or less. If the average thickness of the anti-glare layer 12 is above or below the aforementioned lower limit, the strength of the optical film 10A is improved, and the freedom of the average particle size of the particles it can contain is increased, thus increasing the freedom of adjusting the irregular shape. If the average thickness of the anti-glare layer 12 is below the aforementioned upper limit, warping caused by the curing shrinkage of the resin constituting the anti-glare layer 12 can be suppressed, making molding easier and forming irregularities easier. In addition, it is also easier to achieve functions such as antibacterial and antiviral properties.
[0048] The anti-glare layer 12 comprises resin 13 and microparticles 14. Resin 13 is a photocurable resin or a thermocurable resin. Microparticles 14 are dispersed in resin 13, and the surface irregularities of the anti-glare layer 12 correspond to the dispersion of microparticles 14. It should be noted that the dispersion of microparticles 14 includes not only the state where each microparticle 14 is individually located away from other microparticles 14, but also the state where a group of microparticles 14 aggregated through coagulation is located away from other microparticles 14, or a group of individual microparticles 14. In other words, microparticles 14 can be dispersed individually or in groups within the anti-glare layer 12.
[0049] Resin 13 is preferably a photocurable resin, i.e., a cured form of a photopolymerizable compound. The photopolymerizable compound is an ultraviolet-curable compound or an electron beam-curable compound. One photopolymerizable compound may be used alone, or two or more may be used in combination. Examples of photopolymerizable compounds include monofunctional, difunctional, or trifunctional (meth)acrylate compounds and urethane (meth)acrylate compounds. Furthermore, "(meth)acrylate" is a general term for acrylates and methacrylates. Similarly, hereinafter, "(meth)acryloyl" is a general term for acryloyl and methacryloyl groups, and "(meth)acrylate" is a general term for acrylates and methacrylates.
[0050] Monofunctional (meth)acrylate compounds are compounds having one (meth)acryloyl group, such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, glycidyl (meth)acrylate, acryloylmorpholine, N-vinylpyrrolidone, tetrahydrofurfuryl acrylate, cyclohexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, and isobutyl (meth)acrylate. Borneol ester, isodecyl methacrylate, lauryl methacrylate, tridecyl methacrylate, cetyl methacrylate, stearyl methacrylate, benzyl methacrylate, 2-ethoxyethyl methacrylate, 3-methoxybutyl methacrylate, ethyl carbitol methacrylate, meth phosphate, ethylene oxide modified meth phosphate, phenoxy (meth) acrylate, ethylene oxide modified phenoxy (meth) acrylate, propylene oxide modified phenoxy (meth) acrylate Methacrylate, nonylphenol (meth)acrylate, ethylene oxide modified nonylphenol (meth)acrylate, propylene oxide modified nonylphenol (meth)acrylate, methoxydiethylene glycol (meth)acrylate, methoxypolyethylene glycol (meth)acrylate, methoxypropylene glycol (meth)acrylate, 2-(meth)acryloyloxyethyl-2-hydroxypropyl phthalate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, 2-(meth)acryloyloxyethyl hydrogen phthalate, 2-(meth)propane Acryloyloxypropyl hydrogen phthalate, 2-(meth)acryloyloxypropyl hexahydrophthalate, 2-(meth)acryloyloxypropyl tetrahydrophthalate, dimethylaminoethyl (meth)acrylate, trifluoroethyl (meth)acrylate, tetrafluoropropyl (meth)acrylate, hexafluoropropyl (meth)acrylate, octafluoropropyl (meth)acrylate, 2-adamantane, adamantane-derived adamantanediol-derived mono(meth)acrylates, and other adamantane derivative mono(meth)acrylates, etc.
[0051] Difunctional (meth)acrylate compounds are compounds having two (meth)acryloyl groups, such as ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, butanediol di(meth)acrylate, hexanediol di(meth)acrylate, nonanediol di(meth)acrylate, ethoxylated hexanediol di(meth)acrylate, propoxylated hexanediol di(meth)acrylate, triethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, ethoxylated neopentyl glycol di(meth)acrylate, hydroxypentyl acid neopentyl glycol di(meth)acrylate, etc.
[0052] (Meth)acrylate compounds with three or more functional groups are compounds having three or more (meth)acryloyl groups, such as trimethylolpropane tri(meth)acrylate, ethoxylated trimethylolpropane tri(meth)acrylate, propoxylated trimethylolpropane tri(meth)acrylate, tri(2-hydroxyethyl)isocyanurate tri(meth)acrylate, glycerol tri(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol tri(meth)acrylate, bis(trimethylolpropane)acrylate, etc., which are trifunctional ( Methacrylate compounds; pentaerythritol tetra(meth)acrylate, bis(trimethylolpropane)tetra(meth)acrylate, dipentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, bis(trimethylolpropane) penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, bis(trimethylolpropane) hexa(meth)acrylate, etc., which are 4 or more functional (meth)acrylate compounds; and polyfunctional (meth)acrylate compounds obtained by substituting a portion of these (meth)acrylates with alkyl groups or ε-caprolactones.
[0053] Carbamate (meth)acrylate compounds are, for example, compounds obtained by reacting an isocyanate monomer or prepolymer with a polyester polyol and then reacting the product with a (meth)acrylate monomer having hydroxyl groups.
[0054] Examples of urethane (meth)acrylate compounds include pentaerythritol triacrylate hexamethylene diisocyanate urethane prepolymer, pentaerythritol pentaacrylate hexamethylene diisocyanate urethane prepolymer, pentaerythritol triacrylate toluene diisocyanate urethane prepolymer, pentaerythritol pentaacrylate toluene diisocyanate urethane prepolymer, pentaerythritol triacrylate isophorone diisocyanate urethane prepolymer, and pentaerythritol pentaacrylate isophorone diisocyanate urethane prepolymer.
[0055] The microparticles 14 are organic or inorganic microparticles. The anti-glare layer 12 may contain one type of microparticle 14, and at least one of the material and average particle size may be two or more different types. The average particle size of the microparticles 14 is preferably 80% or less of the thickness of the region of the anti-glare layer 12 that does not contain microparticles 14, more preferably 30% or more and 80% or less. The content of microparticles 14 in the anti-glare layer 12 is preferably 1.0% by mass or more and 15% by mass or less. When the proportion of microparticles 14 is 1.0% by mass or more, it is easy to sufficiently form unevenness; when the proportion of microparticles 14 is 15% by mass or less, it is easy to maintain the optical properties and mechanical properties such as haze in the optical film 10A well.
[0056] Organic microparticles are resin particles formed from light-transmitting resin materials such as acrylic resin, polystyrene resin, styrene-(meth)acrylate copolymer, polyethylene resin, epoxy resin, silicone resin, polyvinylidene fluoride, and polyvinyl fluoride resin.
[0057] Inorganic microparticles can be used as materials to regulate the sedimentation and aggregation of organic microparticles. Examples of inorganic microparticles include silica microparticles, metal oxide microparticles, and mineral microparticles. Examples of silica microparticles include colloidal silica and silica microparticles surface-modified with reactive functional groups such as (meth)acryloyl groups. Examples of metal oxides constituting metal oxide microparticles include alumina, zinc oxide, tin oxide, antimony oxide, indium oxide, titanium dioxide, and zirconium dioxide. Examples of minerals constituting mineral microparticles include mica, synthetic mica, vermiculite, montmorillonite, iron montmorillonite, bentonite, bedesite, soapstone, lithium montmorillonite, magnesia, chloroform, sodium silicate, illite, sodium silicate, layered titanate, montmorillonite, and synthetic montmorillonite. Minerals can be natural, synthetic, or a mixture of natural and synthetic substances. Synthetic substances can contain substitutes and derivatives. Layered organic clays are preferred. Layered organic clays have a structure that introduces organic onium ions into the interlayer of bentonite clay. The type of organic onium ions is not limited as long as they can be introduced into the bentonite clay using its cation exchange capacity. When using particles composed of layered organic clay as mineral particles, synthetic montmorillonite is preferred. Synthetic montmorillonite increases the viscosity of the coating liquid used to form the anti-glare layer 12, inhibits the sedimentation of organic and inorganic particles, and has the function of adjusting the surface texture of the anti-glare layer 12.
[0058] The anti-glare layer 12 can contain various additives. Examples of additives include antifouling agents, UV absorbers, and antistatic agents. Antifouling agents include leveling agents, oleophobic and hydrophobic agents, and anti-fingerprint agents. Antifouling agents may contain fluorinated compounds or silicone compounds. By containing additives, the anti-glare layer 12 can perform various functions such as antifouling, UV absorption, and antistatic properties.
[0059] In the first example of the optical film 10A, the anti-glare layer 12 further contains a functional component that is at least one of an antibacterial agent and an antiviral agent. The anti-glare layer 12 may contain one or more functional components. The content of the functional component in the anti-glare layer 12 is preferably 0.1% by mass or more and 50% by mass or less. If the proportion of the functional component is within the above range, the optical and mechanical properties of the optical film 10A can be well maintained along with the antibacterial and antiviral properties.
[0060] Functional ingredients can function as either antibacterial agents or antiviral agents, or as both antibacterial and antiviral agents, or their function as antibacterial agents or antiviral agents can change depending on factors such as the amount added.
[0061] The functional component can be an inorganic or organic material. Furthermore, the functional component can be particulate or non-particulate. When the functional component is particulate, its average particle size is preferably 1 μm or less. Particulate functional components are mostly inorganic materials, which have a large refractive index difference with the resin 13 of the anti-glare layer 12. However, if the average particle size of the functional component is 1 μm or less, it can suppress the visual recognition of the functional component in the optical film 10A as a bright spot. In addition, organic functional components mostly do not have a particulate form, thus suppressing the occurrence of appearance defects in the optical film 10A such as bright spots.
[0062] The functional components of the inorganic system include metals such as silver, copper, and zinc; metal oxides such as zinc oxide; and metal hydroxides such as calcium hydroxide. These metals can be in the form of metal particles, ions, complexes, or salts. Furthermore, these metals can also be supported on a carrier. Examples of carriers include phosphate-based carriers such as zeolites and zirconium phosphate, silica gel, activated carbon, and glass materials.
[0063] In addition, the functional components of the inorganic system can also be compounds that do not act as photocatalysts, such as titanium dioxide or titanium oxide. These compounds can be used in combination with the aforementioned metals.
[0064] Of the above, inorganic particles containing metals or metal oxides are preferred as functional components of the inorganic system, and materials containing silver are particularly preferred.
[0065] Organic functional components can be either synthetic or natural. Examples of synthetic components include quaternary ammonium salts, biguanide compounds such as polyhexamethylene biguanide, and triclosan. Examples of natural components include physalisol and terpenes.
[0066] Figure 2This is a second example of the layer composition of the optical film 10. In addition to the substrate 11 and the anti-glare layer 12, the optical film 10B of the second example of the optical film 10 also includes a low refractive index layer 15. The low refractive index layer 15 has a lower refractive index than the anti-glare layer 12 and has the function of suppressing surface reflection of the optical film 10B by utilizing light interference.
[0067] The low-refractive-index layer 15 is located on the anti-glare layer 12 and has an uneven surface shape that follows the surface of the anti-glare layer 12. The surface of the low-refractive-index layer 15 opposite to the surface in contact with the anti-glare layer 12 is the surface of the low-refractive-index layer 15, which is the surface of the optical film 10B. The low-refractive-index layer 15 is thinner than the anti-glare layer 12. The average thickness of the low-refractive-index layer 15 is preferably 30 nm or more and 300 nm or less. If the average thickness of the low-refractive-index layer 15 is 30 nm or more, light interference is easily generated; if the average thickness of the low-refractive-index layer 15 is 300 nm or less, scratch resistance and adhesion to the anti-glare layer 12 are easily maintained.
[0068] The low refractive index layer 15 comprises a photocurable resin or a thermocurable resin. The resin comprising the low refractive index layer 15 is preferably a photocurable resin. As the resin material, compounds exemplified as the resin material comprising the anti-glare layer 12 can be used. Alternatively, the low refractive index layer 15 may also comprise a refractive index modifier for reducing the refractive index of the low refractive index layer 15. Examples of refractive index modifiers include fluoride microparticles such as lithium fluoride, magnesium fluoride, sodium hexafluoroaluminate, and aluminum fluoride, as well as silica microparticles. Using silica microparticles, such as porous silica microparticles or hollow silica microparticles, with internal pores, is effective in reducing the refractive index of the low refractive index layer 15.
[0069] The low refractive index layer 15 can contain various additives. Examples of additives include antifouling agents, ultraviolet absorbers, and antistatic agents. Antifouling agents include leveling agents, oleophobic and hydrophobic agents, and anti-fingerprint agents. Antifouling agents may contain fluorinated compounds or silicone compounds in their composition. By containing additives, the low refractive index layer 15 can perform various functions such as antifouling, ultraviolet absorption, and antistatic properties.
[0070] In the second example of the optical film 10B, at least one of the anti-glare layer 12 and the low-refractive-index layer 15 contains a functional component. The components illustrated in the first example can be used as the functional component. The proportion of the functional component relative to the total mass of the anti-glare layer 12 and the low-refractive-index layer 15 is preferably 0.1% by mass or more and 50% by mass or less. If the proportion of the functional component is within the above range, the antibacterial, antiviral, and optical and mechanical properties of the optical film 10B can be well maintained.
[0071] The anti-glare layer 12 is thicker than the low refractive index layer 15, so if the anti-glare layer 12 contains functional components, a higher degree of freedom in adjusting the content of the functional components can be obtained. On the other hand, if the low refractive index layer 15 contains functional components, the functional components are distributed near the surface of the optical film 10B, so it is easy to obtain a higher antibacterial / antiviral effect.
[0072] [Properties of optical films]
[0073] As a characteristic of the optical film 10, the characteristics obtained by analyzing the surface shape using a two-dimensional Fourier transform will be explained. The analysis of the surface shape is performed according to the following steps.
[0074] (i) Obtain three-dimensional data regarding the surface shape of the optical film 10. The three-dimensional data contains information on the height of the unevenness at various locations on the surface of the optical film 10. The three-dimensional data is obtained by measuring the surface shape of the optical film 10 using an optical interferometric or contact measuring device. Representative examples of optical interferometric measuring devices are white light interferometers or laser microscopes, while representative examples of contact measuring devices are surface roughness meters or scanning probe microscopes.
[0075] (ii) Using the above three-dimensional data, a Fast Fourier Transform (FFT) is performed. That is, the wave formed by the change in the height of the surface of the optical film 10 is decomposed into spatial frequency components.
[0076] For example, based on the aforementioned three-dimensional data, a grayscale image is generated that represents height information as brightness levels of a specified grayscale. Specifically, for example, a grayscale image is generated by converting the height information into brightness levels of 256, with a minimum value of 0 and a maximum value of 255. Then, a two-dimensional Fourier transform is performed on the grayscale image. By performing the inverse transform of the power spectrum intensity on the obtained image, the power spectrum intensity is restored to a value corresponding to the height. Thus, data on the height information of the unevenness at various locations on the surface of the optical film 10, for which a fast Fourier transform has been applied, is obtained.
[0077] Alternatively, a two-dimensional Fourier transform can be performed by treating the height information itself as the object of processing, without transforming it into light or dark.
[0078] There are no particular limitations on the number of pixels in the 3D data, grayscale image, and FFT image as a power spectrum. For example, when performing a 2D Fourier transform on a 640px × 480px image to generate a 1024px × 1024px FFT image, after decomposing the 480 column height data into 1024 frequencies for each row, a transpose is performed, and then the 640 column height data for each row is decomposed into 1024 frequencies. This yields a 1024px × 1024px FFT image.
[0079] (iii) For the power spectrum obtained by the above fast Fourier transform, any direction passing through the origin (where the spatial frequency is 0) is set as the object direction, and the power spectrum intensity is output for each spatial frequency of the object direction. The power spectrum intensity is the value after a logarithmic transformation using the common logarithm. The surface of the optical film 10 has an irregular shape, and no periodicity in a specific direction is detected in the power spectrum. Therefore, the intensity distribution in the power spectrum is the same regardless of which direction is taken as the object direction. In addition, to remove noise, the average power spectrum intensity near the spatial frequency of the object can also be used as the power spectrum intensity at that spatial frequency.
[0080] For example, for an image representing the power spectrum described above, an x-axis is set in the horizontal direction passing through the origin, and the range of x>0 and ±20 pixels in the vertical direction from the x-axis is defined as the object region. Then, the value obtained by averaging the power spectrum intensity for each x-coordinate within the object region is set as the power spectrum intensity of the spatial frequency corresponding to each x-coordinate.
[0081] Figure 3 This is a typical example of the power spectrum in the object direction obtained by analyzing the surface shape of the optical film 10 of this embodiment. At each spatial frequency, a higher power spectrum intensity indicates a greater height of the irregularity or convexity within the period corresponding to that spatial frequency.
[0082] exist Figure 3 In the example shown, the higher the spatial frequency, the lower the power spectral intensity, and no prominent peaks were observed at specific spatial frequencies regarding the power spectral intensity. Therefore, it can be said that the smaller the period of the concave-convex structure, the smaller the height of the concave-convex structure tends to be. This tendency arises because the concave-convex structure with a large period is located in the portion where particles 14 are aggregated, and thus the height is larger. Furthermore, as mentioned above, since there are portions where particles 14 are aggregated, portions where particles 14 are individually dispersed, and portions where particles 14 are absent, i.e., idle portions of particles 14, a power spectral intensity is obtained that decreases with increasing spatial frequency.
[0083] Here, the power spectrum in the object direction satisfies the following conditions 1 and 2.
[0084] (Condition 1) The integral value of the power spectrum intensity in the spatial frequency f range of 0 < f ≤ 150 cycle / mm, i.e., the first intensity integral value A, and the integral value of the power spectrum intensity in the spatial frequency f range of 0 < f ≤ 300 cycle / mm, i.e., the second intensity integral value B, are such that the first intensity integral value A is less than 0.65 relative to the second intensity integral value B (A / B).
[0085] (Condition 2) The integral value of the power spectrum intensity within the spatial frequency f range of 40cycle / mm < f < 60cycle / mm, i.e. the third intensity integral value C, is 130 or above.
[0086] Regarding condition 1, as mentioned above, on the surface of the optical film 10, there is a tendency for the height of irregularities with larger periods to be greater. If the height of such irregularities is too large, the scattering of light on the surface of the optical film 10 becomes stronger, resulting in excessive haze and glare reduction of the optical film 10. In other words, the optical properties of the optical film 10 become poor. If the intensity integral value A / B is less than 0.65, the height of irregularities with larger periods will not be too large, thus good optical properties can be obtained.
[0087] Regarding condition 2, it is confirmed that the height of the bump corresponding to the spatial frequency f around 50 cycles / mm is highly correlated with fingerprint erasure performance. If the third intensity integral value C is above 130, the height of the bump in this range is fully obtained, thus achieving good fingerprint erasure performance in the optical film 10.
[0088] Figure 4 This indicates the relationship between the intensity integral values A / B and C and fingerprint erasure. Each point corresponds to a test example of the optical film, the position of each point represents the intensity integral value, and the concentration of each point represents the evaluation of fingerprint erasure. Fingerprint erasure is evaluated as follows: olive oil is applied to the surface of the optical film, then the olive oil is wiped off, and the color difference ΔE between the surface of the optical film before and after the olive oil application is determined by reflectance spectrophotometry. * ab, measuring ΔE * ab becomes the number of erases less than 0.5. Figure 4 The numerical value recorded in the text represents ΔE. * The number of erasures (ab) is less than 0.5. The smaller the value, the lighter the color of the fingerprint, the higher the fingerprint erasure capability.
[0089] It should be noted that, as an experimental example, 79 samples of optical films with different surface textures were used, the dispersion state of the microparticles 14 in the anti-glare layer 12 was adjusted. The dispersion state of the microparticles 14 was adjusted by changing at least one of the following: the average particle size of the microparticles 14, the proportion of microparticles 14 in the anti-glare layer 12, and the thickness of the anti-glare layer 12.
[0090] according to Figure 4 It is known that the larger the third intensity integral value C, the better the fingerprint erasure performance. If the third intensity integral value C is above 130, good fingerprint erasure performance can be obtained. It is believed that by increasing the height of the bumps corresponding to the spatial frequency f around 50 cycles / mm, the bump shape becomes a shape that increases the oil-resistant effect and wiping efficiency of the optical film surface, thus making it easier to remove the oil that constitutes the fingerprint.
[0091] As described above, in this embodiment, by utilizing frequency analysis based on Fast Fourier Transform, as condition 2, the characteristics of the uneven shape are defined by parameters reflecting components highly correlated with fingerprint erasure. Furthermore, by utilizing this frequency analysis, as condition 1, the characteristics of the uneven shape are defined by parameters affecting the scattering properties of the surface of the optical film 10. Therefore, an uneven shape that yields both good optical properties and fingerprint erasure can be accurately determined.
[0092] Of the aforementioned optical properties, anti-glare performance can be evaluated using reflective sharpness at 1° and 5°. Reflective sharpness is the value obtained by subtracting reflective haze (%) from 100. Reflective haze is a parameter representing the degree of diffusion of reflected light. It is determined by illuminating the surface of the optical film 10 on a blackboard with light from a light source position set at an incident angle of approximately 5.7° relative to the normal direction of the surface of the optical film 10, and measuring the intensity distribution of reflected light near the positive reflection direction at the illuminated position. Reflective haze at any angle θ centered on the positive reflection direction is a percentage of the average of the reflective intensity at angle +θ and angle -θ relative to the reflective intensity at the positive reflection direction. The value obtained by subtracting the aforementioned reflective haze at angle θ from 100 is the reflective sharpness at angle θ. The measurement conditions are as described below; other conditions are measured according to ASTM D5767.
[0093] • Slit width: 1mm
[0094] • Objective lens: 16mm
[0095] • Distance from the surface of the optical film to the light-receiving position: 300mm
[0096] In the optical film 10, it is preferable that the reflection sharpness at an angle θ of 1° is 90° or less, and the reflection sharpness at an angle θ of 5° is 70° or more. By making the reflection sharpness at 1° 90° or less and the reflection sharpness at 5° 70° or more, the reflection component relative to the viewing direction can be suppressed, and the reflection component near the viewing direction can be appropriately obtained. Therefore, the image projected onto the surface of the optical film 10 is moderately blurred, thus achieving good anti-glare performance.
[0097] Furthermore, if the reflection sharpness at 1° is below 90 and the reflection sharpness at 5° is above 90, a more moderate expansion of scattered light can be obtained, thus improving the anti-glare performance.
[0098] Furthermore, regarding the aforementioned optical characteristics, the haze specified in JIS K7136 is preferably 5% or more and less than 30%, more preferably 15% or more and less than 25%. This haze refers to the haze that is transmitted. If the haze is within the above range, fogging of the optical film 10 can be suppressed, and therefore, when the optical film 10 is used in a display device, the displayed image can be clearly visually recognized through the optical film 10.
[0099] [Manufacturing methods for optical films]
[0100] As a method for manufacturing the optical film 10, the use of a photopolymerizable compound in the materials of the anti-glare layer 12 and the low refractive index layer 15 will be described.
[0101] The optical film 10A of the first example is formed by coating a coating liquid for forming an anti-glare layer 12 onto a substrate 11, i.e., an anti-glare layer coating liquid, and then curing the coating film.
[0102] The anti-glare coating liquid contains the aforementioned photopolymerizable compound, microparticles 14, functional ingredients, a photopolymerization initiator, and a solvent. If the anti-glare layer 12 contains additives, the anti-glare coating liquid also contains additives.
[0103] When using (meth)acrylates as photopolymerizable compounds, the photopolymerizable compounds in the coating liquid can be monomers or oligomers formed by partial polymerization.
[0104] As photopolymerization initiators, acetophenone-based compounds, alkylphenyl ketone-based compounds, benzoin-based compounds, benzophenone-based compounds, oxime ester-based compounds, thioxanone-based compounds, etc., can be used. These photopolymerization initiators can be used alone or in combination of two or more.
[0105] As a solvent, it can be appropriately selected from aromatic hydrocarbons, hydrocarbons, ethers, ketones, esters, cellosols, alcohols, water, etc., taking into account their coating compatibility.
[0106] There are no particular limitations on the application method of the coating liquid; any well-known wet coating method can be used. The photopolymerizable compound is polymerized by irradiating the coating film with ultraviolet light or other light, thereby curing the coating film and forming the anti-glare layer 12.
[0107] By changing the average particle size of the particles 14, the amount of particles 14 added to the coating solution, the thickness of the coating film, and adjusting the aggregation state of the particles 14 during the preparation or application of the coating solution, the dispersion state of the particles 14 in the anti-glare layer 12 can be altered, thereby changing the surface irregularity of the optical film 10. In other words, by adjusting the dispersion state of the particles 14, an optical film 10A with a surface shape having intensity integral values A, B, and C within a desired range can be manufactured.
[0108] The second example of the optical film 10B is formed by forming an anti-glare layer 12 on a substrate 11, and then coating the surface of the anti-glare layer 12 with a coating liquid for forming a low refractive index layer 15, i.e., a low refractive index layer coating liquid, and then curing the coating film.
[0109] The low-refractive-index layer coating liquid contains the aforementioned photopolymerizable compound, as well as a photopolymerization initiator and a solvent. If the anti-glare layer 12 contains a refractive index adjuster and additives, the low-refractive-index layer coating liquid also contains a refractive index reducer and additives. As the photopolymerization initiator and solvent, photopolymerization initiators and solvents exemplified as materials used in the anti-glare layer coating liquid can be used. The functional component need only be included in at least one of the anti-glare layer coating liquid and the low-refractive-index layer coating liquid.
[0110] There are no particular limitations on the coating method; any known wet coating method can be used. The photopolymerizable compound is polymerized by irradiating the coating with ultraviolet light, thereby curing the coating and forming a low-refractive-index layer 15.
[0111] In the second example, similarly to the first example, by adjusting the dispersion state of the particles 14 in the anti-glare layer 12, it is possible to manufacture an optical film 10B with a surface shape having intensity integral values A, B, and C within the desired range.
[0112] [Display device]
[0113] like Figure 5 As shown, the display device 100 includes an optical film 10 and a main body 20 with image display function. The display surface 20S, which is the surface of the main body 20, is the surface for displaying images, and is the surface of a display panel such as a liquid crystal panel or an organic EL panel, or the surface of a touch panel laminated on the display panel. The optical film 10 is located on the display surface 20S, and the back of the optical film 10 is attached to the display surface 20S.
[0114] In particular, when the display surface 20S is a touch panel surface, the user frequently touches the display device 100, so the optical film 10 has high advantages in terms of fingerprint wiping, antibacterial and antiviral properties.
[0115] Specific examples of display device 100 include smartphones, tablet terminals, personal computers, portable game consoles, music playback devices, televisions, monitors, e-book reading terminals, digital cameras, head-mounted displays, navigation devices, copiers, fax machines, printers, multifunction printers, vending machines, automatic cash deposit machines (ATMs), personal authentication devices, optical communication devices, etc.
[0116] [Example]
[0117] The optical films described above will be explained using specific embodiments and comparative examples.
[0118] (Example 1)
[0119] <Preparation of Anti-glare Coating>
[0120] Organic microparticles formed from cross-linked polymethyl methacrylate (manufactured by Sekisui Chemicals: Techpolymer SSX-2035, average particle size: 3.5 μm) were added to toluene and dispersed using a paint stirrer for 40 minutes. Then, 6.0 parts by weight of the above organic microparticles, 86.0 parts by weight of pentaerythritol triacrylate (PETA) (manufactured by Osaka Organic Chemicals: Viscoat #300) as a photopolymerizable compound, 3.0 parts by weight of photopolymerization initiator (manufactured by IGM Resins BV: Omnirad 184), and 5.0 parts by weight of silver-based antibacterial and antiviral agent (manufactured by Dainippon Seika: particles dispersed by bead milling of PTC-NT(ST), average particle size: 0.5 μm, concentration: 25% by weight) as a functional component were mixed with toluene as a solvent, such that the total solids content in the coating liquid was 50% by weight. The mixture was stirred using a paint stirrer for 40 minutes to prepare an anti-glare coating liquid. It should be noted that the mass fractions of each material mentioned above represent the relative mass ratio of each material.
[0121] <Preparation of coating liquid for low refractive index layer>
[0122] A coating solution for a low refractive index layer was prepared by mixing 45.0 parts by weight of PETA (manufactured by Osaka Organic Chemical Industry: Viscoat #300) as a photopolymerizable compound, 50.0 parts by weight of hollow silica microparticles (average particle size: 75 nm) as a refractive index modifier dispersed in isopropanol, 3.0 parts by weight of photopolymerization initiator (manufactured by IGM Resins BV: Omnirad 184), and 2.0 parts by weight of fluorinated antifouling agent (manufactured by Shin-Etsu Chemical Industry: KY-1203) as an additive. The mixture was diluted with isopropanol as a solvent to achieve a total solids content of 3.5% by weight in the coating solution. The mixture was stirred for 40 minutes using a paint stirrer. It should be noted that the mass fractions of the materials listed above represent the relative mass ratios of the materials.
[0123] <Formation of Optical Films>
[0124] An anti-glare coating solution was applied to the surface of a triacetyl cellulose membrane (Fujifilm: TJ40, thickness: 60 μm) as the substrate using a rod coater to form a coating film. The film thickness was set to 4 μm. After drying the coating film at 100°C for 1 minute using a dryer, it was then subjected to exposure at a cumulative exposure of 200 mJ / cm² in a nitrogen atmosphere (oxygen concentration below 500 ppm) using a high-pressure mercury UV device. 2 The coating is cured by irradiating it with ultraviolet light, thus forming an anti-glare layer.
[0125] Next, a low-refractive-index coating liquid is applied to the surface of the anti-glare layer using a bar coater to form a coating film. Then, the coating film is dried in a dryer at 100°C for 1 minute, and subsequently exposed to a nitrogen atmosphere (oxygen concentration below 500 ppm) using a high-pressure mercury UV device with a cumulative exposure of 200 mJ / cm². 2 The coating is cured by irradiating it with ultraviolet light. This forms a low-refractive-index layer with an optical thickness (refractive index n × film thickness d) that is 1 / 4 of the wavelength of 550 nm.
[0126] Based on the above steps, the optical film of Example 1, which has a substrate, an anti-glare layer and a low refractive index layer, is obtained.
[0127] (Example 2)
[0128] Except that a low refractive index layer is not formed, the optical film of Example 2 is obtained using the same materials and processes as in Example 1.
[0129] (Example 3)
[0130] The microparticles added to the anti-glare coating liquid were changed to organic microparticles formed by cross-linked styrene (Sōken Chemical Manufacturing: SX-500H, average particle size: 5.0 μm), and the film thickness of the coating film formed by the anti-glare coating liquid was changed to 4.5 μm. Otherwise, the optical film of Example 3 was obtained by using the same materials and processes as in Example 1.
[0131] (Example 4)
[0132] Except that a low refractive index layer is not formed, the optical film of Example 4 is obtained using the same materials and processes as in Example 3.
[0133] (Example 5)
[0134] The amount of organic microparticles added to the anti-glare coating liquid was changed to 15 parts by mass. Otherwise, the optical film of Example 5 was obtained by using the same materials and processes as in Example 1.
[0135] (Example 6)
[0136] Except for not forming a low refractive index layer, the optical film of Example 6 was obtained using the same materials and processes as in Example 5.
[0137] (Example 7)
[0138] The functional component added to the anti-glare coating liquid was changed to a silver-based antibacterial and antiviral agent (Dainichi Seika: PTC-NT(S1), average particle size: 1.0 μm). Otherwise, the optical film of Example 7 was obtained using the same materials and processes as in Example 1.
[0139] (Example 8)
[0140] Except that a low refractive index layer is not formed, the optical film of Example 8 is obtained using the same materials and processes as in Example 7.
[0141] (Example 9)
[0142] The functional component added to the anti-glare coating liquid was changed to a quaternary ammonium salt antibacterial and antiviral agent (manufactured by Kobayashi Pharmaceutical: KOBA-GUARD). Otherwise, the optical film of Example 9 was obtained using the same materials and processes as in Example 1.
[0143] (Example 10)
[0144] Except that a low refractive index layer is not formed, the optical film of Example 10 is obtained using the same materials and processes as in Example 9.
[0145] (Example 11)
[0146] The microparticles added to the anti-glare coating solution were changed to organic microparticles formed from cross-linked styrene (Sōken Chemical Manufacturing: SX-500H, average particle size: 5.0 μm), the film thickness of the coating formed by the anti-glare coating solution was changed to 4.5 μm, and the functional component added to the anti-glare coating solution was changed to a quaternary ammonium salt antibacterial and antiviral agent (Kobayashi Pharmaceutical Manufacturing: KOBA-GUARD). Except for these changes, the optical film of Example 11 was obtained using the same materials and processes as in Example 1. Example 11 differs from Example 3 only in its functional component.
[0147] (Example 12)
[0148] Except that a low refractive index layer is not formed, the optical film of Example 12 is obtained using the same materials and processes as in Example 11.
[0149] (Example 13)
[0150] The amount of organic microparticles added to the anti-glare coating liquid was changed to 15 parts by weight, and the functional component added to the anti-glare coating liquid was changed to a quaternary ammonium salt antibacterial and antiviral agent (manufactured by Kobayashi Pharmaceutical: KOBA-GUARD). Otherwise, the optical film of Example 13 was obtained using the same materials and processes as in Example 1. Example 13 differs from Example 5 only in its functional component.
[0151] (Example 14)
[0152] Except that a low refractive index layer is not formed, the optical film of Example 14 is obtained using the same materials and processes as in Example 13.
[0153] (Example 15)
[0154] The functional component added to the anti-glare coating liquid was changed to a silver-based antibacterial and antiviral agent (Dainichi Seika: PTC-NT(ST), average particle size: 3.0 μm). Otherwise, the optical film of Example 15 was obtained using the same materials and processes as in Example 1.
[0155] (Example 16)
[0156] Except that a low refractive index layer is not formed, the optical film of Example 16 is obtained using the same materials and processes as in Example 15.
[0157] (Example 17)
[0158] The microparticles added to the anti-glare coating liquid were changed to organic microparticles formed by cross-linked styrene (Sōken Chemical Manufacturing: SX-500H, average particle size: 5.0 μm), the film thickness of the coating formed by the anti-glare coating liquid was changed to 4.5 μm, and the functional component added to the anti-glare coating liquid was changed to a silver-based antibacterial and antiviral agent (Dai Nippon Seika Manufacturing: PTC-NT(ST), average particle size: 3.0 μm). Otherwise, the optical film of Example 17 was obtained by using the same materials and processes as in Example 1.
[0159] Example 17 differs from Example 3 only in its functional components.
[0160] (Example 18)
[0161] Except for not forming a low refractive index layer, the optical film of Example 18 was obtained using the same materials and processes as in Example 17.
[0162] (Example 19)
[0163] The amount of organic microparticles added to the anti-glare coating liquid was changed to 15 parts by weight, and the functional component added to the anti-glare coating liquid was changed to a silver-based antibacterial and antiviral agent (Dainichi Seika: PTC-NT(ST), average particle size: 3.0 μm). Otherwise, the optical film of Example 19 was obtained using the same materials and processes as in Example 1. Example 19 differs from Example 5 only in its functional component.
[0164] (Example 20)
[0165] Except that a low refractive index layer is not formed, the optical film of Example 20 is obtained using the same materials and processes as in Example 19.
[0166] (Comparative Example 1)
[0167] The microparticles added to the anti-glare coating liquid were changed to organic microparticles formed by cross-linked styrene (Sōken Chemical Manufacturing: SX-130H, average particle size: 1.3 μm), the amount of organic microparticles added to the anti-glare coating liquid was changed to 3 parts by mass, the total amount of functional components added to the anti-glare coating liquid was replaced with PETA, and the film thickness of the coating formed by the anti-glare coating liquid was changed to 6 μm. Otherwise, the optical film of Comparative Example 1 was obtained by using the same materials and processes as in Example 1.
[0168] (Comparative Example 2)
[0169] Except that a low refractive index layer is not formed, the optical film of Comparative Example 2 is obtained using the same materials and processes as Comparative Example 1.
[0170] (Comparative Example 3)
[0171] The amount of organic microparticles added to the anti-glare coating liquid was changed to 10 parts by mass, and the total amount of functional components added to the anti-glare coating liquid was replaced with PETA. Otherwise, the optical film of Comparative Example 3 was obtained using the same materials and processes as in Example 1.
[0172] (Comparative Example 4)
[0173] Except that a low refractive index layer is not formed, the optical film of Comparative Example 4 is obtained using the same materials and processes as Comparative Example 3.
[0174] (Comparative Example 5)
[0175] The total amount of functional components added to the anti-glare coating liquid was replaced with PETA, and the film thickness of the coating formed by the anti-glare coating liquid was changed to 5 μm. Otherwise, the optical film of Comparative Example 5 was obtained using the same materials and processes as in Example 1.
[0176] (Comparative Example 6)
[0177] Except that a low refractive index layer is not formed, the optical film of Comparative Example 6 is obtained using the same materials and processes as Comparative Example 5.
[0178] (Comparative Example 7)
[0179] The microparticles added to the anti-glare coating liquid were changed to organic microparticles formed by cross-linked styrene (Sōken Chemical Manufacturing: SX-500H, average particle size: 5.0 μm), the amount of organic microparticles added to the anti-glare coating liquid was changed to 10 parts by mass, and the film thickness of the coating film formed by the anti-glare coating liquid was changed to 6 μm. Otherwise, the optical film of Comparative Example 7 was obtained by using the same materials and processes as in Example 1.
[0180] (Comparative Example 8)
[0181] Except that a low refractive index layer is not formed, the optical film of Comparative Example 8 is obtained using the same materials and processes as Comparative Example 7.
[0182] (Comparative Example 9)
[0183] The microparticles added to the anti-glare coating liquid were changed to organic microparticles formed from cross-linked polymethyl methacrylate (Sekisui Chemicals Industrial Products: SSX-102, average particle size: 2.5 μm), the amount of organic microparticles added to the anti-glare coating liquid was changed to 8 parts by mass, and the film thickness of the coating formed by the anti-glare coating liquid was changed to 5 μm. Otherwise, the optical film of Comparative Example 9 was obtained using the same materials and processes as in Example 1.
[0184] (Comparative Example 10)
[0185] Except that a low refractive index layer is not formed, the optical film of Comparative Example 10 is obtained using the same materials and processes as Comparative Example 9.
[0186] (Evaluation Method)
[0187] <Surface Shape>
[0188] For the optical films of each embodiment and each comparative example, the surface shape was analyzed according to the following steps.
[0189] (1) The surface shape of the optical film was measured using a white light interferometer (Vertscan R3300H Lite) to obtain three-dimensional data. The measurement area was a rectangular region of 940.8 μm × 705.6 μm. The number of pixels was 640px × 480px, and the pixel size corresponding to the resolution in both directions was 1.47 μm per pixel.
[0190] (2) Use the image analysis software "ImageJ 1.53h" to perform FFT analysis. The steps are as follows.
[0191] (2-1) The three-dimensional data is taken as TIF image data and entered into the above image analysis software.
[0192] (2-2) In the image analysis software described above, select "FFT Options" to check the "Raw Power Spectrum". Then, perform a Fast Fourier Transform (FFT) process. This will open an image titled "FFT of (filename)" and an image titled "PS of (filename)". Each image is 1024px × 1024px in size. The "FFT of (filename)" image represents the power spectrum intensity normalized to 256 gray levels, while the "PS of (filename)" image represents the power spectrum intensity set to values corresponding to the height of the three-dimensional data.
[0193] (2-3) Turn off the "FFT of (filename)" image, and apply the commands "Log" and "Macro..." to the "PS of (filename)" image respectively, with the code "v = v / 2.303;". This will logarithmically transform the z-axis representing the power spectrum intensity and its values using the common logarithm.
[0194] (2-4) For the image processed in (2-3) above, with the image center as the origin, set the x-axis in the horizontal direction passing through the origin, specify x>0 and a range of ±20 pixels in the vertical direction on the x-axis, and output the power spectral intensity of each pixel. Then, calculate the average power spectral intensity of pixels with the same x-coordinate, and use it as the power spectral intensity of each x-coordinate.
[0195] (2-5) Based on the pixel size of the three-dimensional data, the x-coordinate of the output power spectrum intensity is transformed into a spatial frequency with a length of 1 mm.
[0196] (2-6) Calculate the intensity integral values A, B, and C based on the power spectral intensity of each spatial frequency.
[0197] <Anti-glare>
[0198] For the optical films of each embodiment and comparative example, anti-glare performance was evaluated by measuring reflective sharpness at 1° and 5°. Each reflective sharpness was measured using a display measurement system (DM&S: SMS-1000) with the back of the optical film adhered to a blackboard with optical adhesive as the object, under the conditions described below. It should be noted that conditions other than those described below were measured according to ASTM D5767.
[0199] • Width of the slit for the light source: 1mm
[0200] • Objective lens: 16mm
[0201] • Distance between the surface of the optical film and the receiving camera: 300mm
[0202] In the evaluation of anti-glare performance, a case where the reflection sharpness at 1° is below 90 and the reflection sharpness at 5° is above 90 is designated as "Excellent" (◎); a case where the reflection sharpness at 1° is below 90 and the reflection sharpness at 5° is above 70 but below 90 is designated as "Good" (○); and a case where at least one of the following conditions is met: a reflection sharpness at 1° is above 90 and a reflection sharpness at 5° is below 70 is designated as "Poor" (×). "Poor" includes situations where the surrounding image is clearly reflected on the optical film and situations where the image reflected on the optical film is excessively blurry.
[0203] <Haze>
[0204] The haze of the optical films in each embodiment and comparative example was measured. The haze was measured using a haze meter (Nippon Denshoku Kogyo: NDH7000) according to JIS K7136. In the haze evaluation, cases with haze of 15% or more but less than 25% were designated as "Excellent" (◎), cases with haze of 5% or more but less than 15% or 25% or more but less than 30% were designated as "Good" (○), and cases with haze less than 5% or more than 30% were designated as "Poor" (×).
[0205] <Appearance>
[0206] For each embodiment and each comparative example, the optical film was visually observed through a three-wavelength fluorescent lamp to evaluate its appearance. In the appearance evaluation, a condition with uniform transparency and no observed dot-like defects as agglomerates or bright spots was designated as good "○", and a condition with at least one of uneven transparency and dot-like defects was designated as bad "×".
[0207] <Reflectivity>
[0208] For the surfaces of the optical films in each embodiment and comparative example, the spectrophotometric reflectance at an incident angle of 5° was measured as reflectance. The reflectance was measured using an automatic spectrophotometer (Hitachi, U-4100). It should be noted that the measurement was performed on the back side of the optical film after anti-reflective treatment by applying a matte black coating.
[0209] In the evaluation of reflectivity, a reflectivity of less than 0.5% is marked as "Excellent" (◎), a reflectivity of 0.5% or more but less than 1% is marked as "Good" (○), and a reflectivity of 1% or more is marked as "Poor" (×).
[0210] It should be noted that the purpose of the reflectivity evaluation is to assess whether the surface reflection is adequately suppressed by the use of an optical film with a low refractive index layer. Therefore, the reflectivity evaluation was not performed for the embodiments and comparative examples in which no low refractive index layer was formed.
[0211] <Fingerprint erasability>
[0212] For the optical films of each embodiment and each comparative example, the fingerprint erasure performance was evaluated according to the following steps.
[0213] (1) Attach the back of the optical film to the blackboard with optical adhesive, and press the artificial leather with olive oil on the surface of the optical film, thereby making the olive oil adhere to the surface of the optical film.
[0214] (2) After wiping away the olive oil adhering to the surface of the optical film with a paper towel (made by Crecia Paper Industries, Japan) with a load of 1 kg, the reflectance spectrophotometry of the optical film surface was performed. Then, the above process of wiping away the olive oil and performing the reflectance spectrophotometry was repeated. It should be noted that the reflectance spectrophotometry was also performed before the olive oil was applied.
[0215] (3) Based on the results of the reflectance spectrophotometry, the color difference ΔE of olive oil on the surface of the optical film before and after each wiping is calculated. * ab, the color difference ΔE *The number of erasures when ab is below 0.5 is defined as the number of erasures completed. Then, fingerprint erasure performance is evaluated based on the number of erasures completed. In the fingerprint erasure performance evaluation, cases with fewer than 5 erasures completed are designated as "Excellent" (◎), cases with 5 to 10 erasures completed are designated as "Good" (○), cases with 10 to 30 erasures completed are designated as "Slightly Poor" (△), and cases with more than 30 erasures completed are designated as "Poor" (×).
[0216] <Sliding>
[0217] For the surfaces of the optical films of each embodiment and each comparative example, the coefficient of kinetic friction was determined under the following conditions in accordance with JIS K 7125.
[0218] • Measuring apparatus: Static and dynamic friction testing machine (Made by Trinity Lab: TL201T t)
[0219] • Probe: A tactile probe with a fingerprint pattern (proposed by Takashi Maeno's laboratory at the Graduate School of Systems Design and Management, Keio University, and Yoshimune Nonomura's laboratory at the Graduate School of Science and Engineering, Yamagata University).
[0220] • Analysis software: Friction analysis software
[0221] • Vertical load: 20g
[0222] • Sliding speed: 10mm / sec
[0223] • Movement distance: 30mm
[0224] • Data collection speed: 1 msec
[0225] In the measurement, an optical film with its back attached to a blackboard was fixed to the stage of the measuring device using adhesive. The coefficient of friction between the tactile contact with the fingerprint pattern and the surface of the optical film was measured under the conditions described above. Then, the average value of the coefficient of friction under sliding conditions, with a movement distance of 10 mm or more and 20 mm or less, was calculated, and the obtained value was taken as the coefficient of kinetic friction μk.
[0226] In the evaluation of slipability, a dynamic friction coefficient μk of 0.3 or less is designated as "good" (○), and a dynamic friction coefficient μk greater than 0.3 is designated as "bad" (×). Furthermore, the tactile contact tip with a fingerprint pattern possesses a hardness comparable to a finger and a raised / lowered pattern similar to an actual fingerprint, allowing for measurement under conditions closely resembling contact with an actual finger. A low dynamic friction coefficient makes it easier for the finger to slide on the surface of the optical film, thus indicating good tactile feedback.
[0227] <Antibacterial properties>
[0228] For the optical films of each embodiment and comparative example, antimicrobial tests were performed against Staphylococcus aureus and Escherichia coli according to JIS Z 2801. Polyethylene film was used as the unprocessed sample. In the evaluation of antimicrobial activity, a value of 2.0 or higher against both Staphylococcus aureus and Escherichia coli was rated as good "○", and a value of less than 2.0 against at least one of Staphylococcus aureus and Escherichia coli was rated as poor "×".
[0229] <Antiviral>
[0230] For the optical films of each embodiment and comparative example, antiviral tests were performed against influenza A virus and feline calicivirus according to ISO 21702. Polyethylene film was used as the unprocessed sample. In the evaluation of antiviral activity, a value of 2.0 or higher against at least one of influenza A virus and feline calicivirus was rated as good "○", and a value of less than 2.0 against both influenza A virus and feline calicivirus was rated as poor "×".
[0231] (Evaluation Results)
[0232] Table 1 shows the evaluation results for each embodiment and each comparative example based on the above evaluation methods.
[0233] Table 1
[0234] As shown in Table 1, under condition 1, i.e., when the intensity integral value A / B is less than 0.65, both anti-glare and haze are good or particularly good. As in Comparative Examples 3, 4, 7, and 8, if the intensity integral value A / B is around 0.65 to 0.70, while anti-glare is good, haze becomes poor. Furthermore, as in Comparative Examples 1 and 2, if the intensity integral value A / B exceeds 0.80, both anti-glare and haze become poor. This suggests that the larger the intensity integral value A / B, the greater the light scattering from the surface of the optical film.
[0235] When condition 2 is met, i.e., when the intensity integral value C is 130 or higher, fingerprint erasure performance is good or particularly good. As in Comparative Examples 1-6, 9, and 10, when the intensity integral value C is less than 130, fingerprint erasure performance becomes poor. Furthermore, regarding each embodiment, comparing the case with and without a low-refractive-index layer, the fingerprint erasure performance is improved when a low-refractive-index layer is present. This is believed to be because the anti-fouling agent contained in the low-refractive-index layer performs an anti-fouling function within the low-refractive-index layer.
[0236] It was confirmed that the higher the fingerprint erasure, the higher the sliding performance. If the intensity integral value C is above 130, the sliding performance also becomes good or particularly good.
[0237] Regarding appearance, the appearance is good when the functional component is an inorganic particle with an average particle size of 1.0 μm or less, and when the functional component is an organic material that does not have a particle shape. As in Examples 15-20, the appearance becomes poor if the functional component is an inorganic particle with an average particle size of more than 1.0 μm.
[0238] Regarding reflectivity, it was confirmed that it was good in all the embodiments and comparative examples in which a low refractive index layer was formed, and surface reflection was suppressed by the low refractive index layer.
[0239] Regarding antibacterial and antiviral properties, it was confirmed that they were good in both the examples and comparative examples containing the functional ingredients, and that the antibacterial and antiviral properties were suitably exerted by the presence of the functional ingredients in the anti-glare layer.
[0240] It should be noted that in optical films, it is not necessarily required that all of the above evaluation items be good or particularly good, depending on the evaluation items that are emphasized in the application.
[0241] As described above in the embodiments and examples, the following effects can be obtained based on the optical film and the display device.
[0242] (1) With an intensity integral value A / B less than 0.65, the optical properties caused by light scattering from the surface of the optical film 10, namely anti-glare and haze, become good. In addition, with an intensity integral value C of 130 or more, good fingerprint removal properties can be obtained.
[0243] (2) In the anti-glare layer 12, the unevenness is formed by containing microparticles 14, so it is easy to form fine unevenness and adjust the shape of the unevenness.
[0244] (3) If the surface of the anti-glare layer 12 is the surface of the optical film 10 and the anti-glare layer 12 contains functional components, the manufacturing process of the optical film 10 can be simplified compared to the case where the layer containing the functional components is set separately from the anti-glare layer 12.
[0245] (4) If a low refractive index layer 15 is stacked on the anti-glare layer 12, light interference will occur, which can suppress the surface reflection of the optical film.
[0246] (5) If the surface of the low refractive index layer 15 is the surface of the optical film 10 and at least one of the anti-glare layer 12 and the low refractive index layer 15 contains a functional component, the manufacturing process of the optical film 10 can be simplified compared to the case where a layer containing a functional component is separately provided outside these layers.
[0247] (6) If the functional component contained in the optical film 10 is at least one of particles containing metal or metal oxide particles with an average particle size of less than 1 μm and organic materials, the functional component can be suppressed from being visually identified as a bright spot or agglomeration point. Therefore, the reduction in the appearance quality of the optical film 10 can be suppressed.
[0248] (7) If the layer containing the surface of the optical film 10 contains an antifouling agent, the antifouling function is performed on the surface of the optical film 10, thus further improving the fingerprint wiping performance. In addition, the antifouling agent can suitably perform the antifouling function by containing at least one of a fluorine compound and a silicone compound.
[0249] (8) If the reflection resolution of 1° in the optical film 10 is less than 90 and the reflection resolution of 5° is more than 70, then good anti-glare performance can be obtained.
[0250] (9) By incorporating the optical film 10 into the display device 100, a display device 100 with good optical properties and fingerprint wiping performance can be obtained. In particular, if the display device 100 is equipped with a touch panel, the benefits of the fingerprint wiping performance, antibacterial properties, and antiviral properties of the optical film 10 can be obtained.
[0251] [Variation Example]
[0252] The above-described embodiments can also be implemented by modification as follows. Furthermore, the following variations can also be combined with each other.
[0253] If conditions 1 and 2 regarding the intensity integral value are satisfied, then the tendency of the power spectrum obtained by the fast Fourier transform of the surface of the optical film 10 can be compared with... Figure 3 The examples shown are different. For instance, regarding power spectral intensity, peaks can be observed at specific spatial frequencies, and the power spectral intensity may not simply decrease with increasing spatial frequency.
[0254] • The layer containing the functional component may not necessarily be the anti-glare layer 12 or the low refractive index layer 15. For example, in the first example of the optical film 10A, a layer containing the functional component may be laminated on the anti-glare layer 12, and in the second example of the optical film 10B, a layer containing the functional component may be laminated on the low refractive index layer 15. In short, as long as the optical film 10 contains the functional component and the surface of the optical film 10 has an unevenness that follows the surface of the anti-glare layer, the layer structure of the optical film 10 may differ from the structure shown in the above embodiments.
[0255] The unevenness of the anti-glare layer 12 is not limited to containing particles 14, but can also be formed by shaping or phase separation of polymers.
[0256] Explanation of reference numerals in the attached figures
[0257] 10, 10A, 10B optical films
[0258] 11 Substrate
[0259] 12 Anti-glare layer
[0260] 13 Resin
[0261] 14 Particles
[0262] 15 Low-refractive-index layer
[0263] 20S display surface
[0264] 100 display devices
Claims
1. An optical film having a surface with irregularities and containing a functional component that is at least one of an antibacterial agent and an antiviral agent. in, When applying a Fast Fourier Transform to the height information of the unevenness at various locations on the surface, the power spectrum in one direction passing through the origin satisfies the following conditions 1 and 2. (Condition 1) The integral value of the power spectrum intensity within the spatial frequency f range of 0 < f ≤ 150 cycles / mm is the first intensity integral value, and the integral value of the power spectrum intensity within the spatial frequency f range of 0 < f ≤ 300 cycles / mm is the second intensity integral value. The first intensity integral value is less than 0.65 relative to the second intensity integral value. (Condition 2) The integral value of the power spectrum intensity in the spatial frequency f range of 40 cycle / mm < f < 60 cycle / mm is the third intensity integral value, and the third intensity integral value is 130 or above.
2. The optical film according to claim 1, comprising a substrate and an anti-glare layer supported by the substrate. The anti-glare layer contains microparticles and has a surface with irregularities corresponding to the dispersion of the microparticles.
3. The optical film according to claim 2, wherein, The surface of the anti-glare layer is the surface of the optical film. The anti-glare layer contains the aforementioned functional components.
4. The optical film according to claim 2, further comprising a low refractive index layer located on the anti-glare layer, The low-refractive-index layer has a lower refractive index than the anti-glare layer and has a surface shape that follows the unevenness of the anti-glare layer.
5. The optical film according to claim 4, wherein, The surface of the low-refractive-index layer is the surface of the optical film. At least one of the anti-glare layer and the low refractive index layer contains the functional component.
6. The optical film according to claim 1, wherein, The functional component of the optical film is a particle containing a metal or metal oxide, and is at least one of particles with an average particle size of less than 1 μm and an organic material.
7. The optical film according to claim 1, wherein, The layer of the optical film that includes the surface contains an antifouling agent.
8. The optical film according to claim 7, wherein, The antifouling agent contains at least one of a fluorinated compound and a silicone compound.
9. The optical film according to claim 1, wherein, The optical film has a reflection resolution of less than 90 at 1° and a reflection resolution of more than 70 at 5°.
10. A display device comprising an optical film according to any one of claims 1 to 9 and a display surface for displaying an image, in, The optical film is located on the display surface.
Citation Information
Patent Citations
Anti-reflection stack
JP2011133905A
Optical laminate, and polarizing plate and image display device using the same
JP2012103701A
Antibacterial film, touch panel, and method for producing antibacterial film
WO2021256560A1